1991
DOI: 10.1002/hup.470060306
|View full text |Cite
|
Sign up to set email alerts
|

Study of effects of clobazam and lorazepam on memory and cognitive functions in healthy subjects

Abstract: This was a double-blind, placebo-controlled crossover study in 15 healthy female volunteers. It consisted of five sessions, separated by 1 week wash-out between sessions. The purpose of the trial was to study the potential amnesic and sedative activity of clobazam and lorazepam, and the potential antagonism between these effects under the joint influence of a high noise level and intense intermittent light stimulation (ILS), aimed at increasing the level of alertness. The study drugs were administered as a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 58 publications
4
10
0
Order By: Relevance
“…The deficit in psychomotor skills peaked 2 to 4 h after dosing and was persistent, being present at the last determination, 8 h post-dosing, for some of the tests used. Similar impairment had already been demonstrated up to 12 h post-dose [12,13,[15][16][17]28]. Lorazepam also impaired short-term memory, as demonstrated by the decrease in the number of words correctly remembered after the first immediate free recall or throughout the 10 learning trials and by the increase in the reaction time recorded in the Steinberg memory scanning test.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The deficit in psychomotor skills peaked 2 to 4 h after dosing and was persistent, being present at the last determination, 8 h post-dosing, for some of the tests used. Similar impairment had already been demonstrated up to 12 h post-dose [12,13,[15][16][17]28]. Lorazepam also impaired short-term memory, as demonstrated by the decrease in the number of words correctly remembered after the first immediate free recall or throughout the 10 learning trials and by the increase in the reaction time recorded in the Steinberg memory scanning test.…”
Section: Discussionsupporting
confidence: 71%
“…Mizolastine, a new benzimidazole derivative, is a more in healthy volunteers has antihistaminic activity selective, peripherally-acting, histamine Hi-receptor (histamine challenge), being most effective at [10][11][12][13][14][15][16][17][18][19][20] antagonist. It is more potent in several animal models mg [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzodiazepine use has been associated with a wide range of cognitive side effects [46,77,78]. Few studies have compared SO and benzodiazepines on cognitive tasks [76][77][78][79], and due to differences in study populations and in cognitive tasks, the data of this study cannot be compared with Carter's data [76,79]. Nevertheless, the present results showed that sedation induced by SMO.IR remained mainly subjective and was less frequently observed in performance tasks.…”
Section: Discussionmentioning
confidence: 55%
“…Levetiracetam (Koo et al, 2013) shows also very favourable cognitive profile. In contrast clobazam (Patat et al, 1991) is known to cause memory impairment in healthy volunteers (at the dose of 30 mg). In patients with epilepsy the data are conflicting because CLB use in drug resistant epilepsies entailed cognitive improvement due to significant seizures reduction; in some studies it is highlighted that the cognitive side-effect profile of CLB is similar to other benzodiazepines but with substantially decreased sedation and increased psychomotor performance (Wheless and Phelps, 2013).…”
Section: Discussionmentioning
confidence: 99%